Anti-aggregation effect of Ascorbic Acid and Quercetin on aggregated Bovine Serum Albumin Induced by Dithiothreitol: Comparison of Turbidity and Soluble Protein Fraction Methods - Amat Rifai; Mukhammad Asy'ari; Agustina L. N. Aminin (Jurnal Kimia Sains dan Aplikasi, 2020)
Studies on the anti-aggregation of dithiothreitol (DTT) induced - protein is generally determined by the fraction soluble (non-aggregated) protein. While the turbidity method is commonly used in studies of anti-aggregation, in which protein is induced by heat, in this study, both methods are compared in observing the anti-aggregation activity of ascorbic acid and quercetin toward bovine serum albumin induced by DTT. The DTT is a reducing agent for protein disulfide bonds and capable of inducing protein aggregation at physiological pH and temperature. The work was performed by the formation of Bovine Serum Albumin (BSA) aggregates induced by DTT under physiological conditions, which are pH 7.4 and 37°C. The aggregated protein profile was observed using the turbidity method at the end of incubation and measuring the difference of concentration between the fraction of soluble protein before and after incubation. The measurement was carried out using a spectrophotometer UV-Vis. The results indicate that both methods show similar inhibition profiles. The potential inhibition of ascorbic acid (AA) toward BSA protein aggregation induced by DTT increased along with incubation time. While quercetin shows the highest inhibition at 12 hours but decreased at 18 hours, this study reveals that both methods can observe the anti-aggregation activity of ascorbic acid and quercetin.